HEMATOLOGICAL ALTERATIONS, OXIDATIVE STRESS, AND APOPTOSIS ASSOCIATED WITH HAIR DYE USE IN JORDANIAN WOMEN (Applied Biological Research, 2026)
Many people both male and female use hair dye to change their hair colour, but theses dyes induce several deteriorating effects like DNA damage, apoptosis and cancers. This study investigated the association of hair dye use and hematological alterations, oxidative damage, and cell death by measuring blood indices and genes expression involved in DNA damage and repair, and apoptotic pathways (XRCC1, p53, cytochrome C, and caspase-9) in women. A total of 50 women, comprising of 25 regular hair dye users and 25 age-matched controls, were enrolled in this case-control study and venous blood samples were collected to evaluate hematological indices and oxidative stress biomarkers (TAC and MDA). Gene expression levels of DNA damage and repair markers (XRCC1 and p53) and apoptosis-related markers (Caspase-9 and Cytochrome C) were quantified in peripheral blood lymphocytes using reverse transcription quantitative PCR. Our findings showed that both Hb levels and RBC count were significantly reduced in hair-dyed group, along with significant elevation in WBC count suggesting the inflammatory response against the chemicals used in hair dyes. In terms of oxidative damage, total antioxidant capacity was significantly depleted along with significant rise in malondialdehyde (MDA) and Caspase-3 levels in women using hair-dyes suggesting the oxidative stress and cell apoptosis mediated by hair dyes. The increased expression of XRCC1, p53, Caspase-9, and cytochrome C further substantiated the opinion that hair dye chemicals induce DNA damage and apoptosis. The findings emphasise on the need for more long-term monitoring of the impacts of exposure to hair colour and raise alarms on the risk of prolonged use of hair dyes.
Keywords: Apoptosis, DNA damage, hair dye, oxidative stress